2020
DOI: 10.1136/annrheumdis-2020-eular.1570
|View full text |Cite
|
Sign up to set email alerts
|

Sat0449 spondyloarthritis and Fracture Risk: Does Dxa Really Have an Impact in the Risk of Fracture Estimated by Frax?

Abstract: Background:Low bone mineral density (BMD) is common in ankylosing spondylitis (AS). The fracture risk (FR) is increased and its reduction with pharmacologic therapy is not clearly defined in this population. However, early screening and bisphosphonates as first-line treatment are recommended.Objectives:To investigate the influence of dual-energy X-ray absorptiometry (DXA) in the ten-year risk of fracture assessed by FR Assessment Tool (FRAX) and to determine possible demographic or clinical factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This process affects bone metabolism in AS patients. A retrospective study found that patients with AS commonly have low bone mineral density (BMD), which may aggravate the symptoms of AS ( 56 ). Therefore, the observed correlation between AS and iron homeostasis indicators may be mediated by increased hepcidin levels during inflammation, which affects iron homeostasis indicators leading to aggravation of AS disease.…”
Section: Discussionmentioning
confidence: 99%
“…This process affects bone metabolism in AS patients. A retrospective study found that patients with AS commonly have low bone mineral density (BMD), which may aggravate the symptoms of AS ( 56 ). Therefore, the observed correlation between AS and iron homeostasis indicators may be mediated by increased hepcidin levels during inflammation, which affects iron homeostasis indicators leading to aggravation of AS disease.…”
Section: Discussionmentioning
confidence: 99%